Corporate Social Responsibility and Green Accounting: Effects on Profitability During COVID-19 in Indonesia - Laksmi Regita Sari; I Made Pande Dwiana Putra (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2026)
The objective of this study is to examine and gather empirical data about the impact of green accounting practices and disclosures regarding social responsibility on industrial firms' profitability in Indonesia during the Covid-19 outbreak. The 189 manufacturing enterprises that were regularly listed on the Indonesia Stock Exchange between 2020 and 2022 comprise the study's population. Purposive sampling was used to identify the research sample, and the results showed that the sample consisted of 45 assessments or 15 enterprises. Multiple linear regression analysis is the method of analysis. The study's findings indicate that while the adoption of green accounting has a favorable impact on profitability, the release of corporate social responsibility has no bearing on it.